2015
DOI: 10.1016/j.pmrj.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Intradiskal Platelet‐Rich Plasma (PRP) Injections: A Prospective, Double‐Blind, Randomized Controlled Study

Abstract: Participants who received intradiskal PRP showed significant improvements in FRI, NRS Best Pain, and NASS patient satisfaction scores over 8 weeks compared with controls. Those who received PRP maintained significant improvements in FRI scores through at least 1 year of follow-up. Although these results are promising, further studies are needed to define the subset of participants most likely to respond to biologic intradiskal treatment and the ideal cellular characteristics of the intradiskal PRP injectate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
169
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(187 citation statements)
references
References 34 publications
1
169
1
3
Order By: Relevance
“…PRP has been utilized in a variety of musculoskeletal indications with evidence of anti-inflammatory and healing properties. One study demonstrated that intradiscal injections of PRP led to symptomatic clinical benefit in individuals with chronic discogenic lower back pain [14]. By combining PRP with SVF, there may be an increased number of growth factors anad proteins which could translate to improved patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…PRP has been utilized in a variety of musculoskeletal indications with evidence of anti-inflammatory and healing properties. One study demonstrated that intradiscal injections of PRP led to symptomatic clinical benefit in individuals with chronic discogenic lower back pain [14]. By combining PRP with SVF, there may be an increased number of growth factors anad proteins which could translate to improved patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective, double-blinded, randomized, placebo controlled study of 47 patients showed significant improvement outcomes in the intradiscal injected PRP group with regard to pain. Function (functional rating index) ( p =0.03) and outcome satisfaction (North American Spine Society) ( p =0.01) were revealed at 8-week follow-up and statistically improved function at the 1-year follow-up 79. Both of these studies conclude with a recommendation for additional trials of intradiscal PRP.…”
Section: Introductionmentioning
confidence: 64%
“…Several studies have demonstrated improvement in clinical scores including ODI, VAS, and JOA beginning 1 month post-PRP injection [64][65][66][67]. Additionally, these studies have reported no complications associated with MSC and PRP injections [64].…”
Section: Treatment Non-operativementioning
confidence: 95%